A Man's Guide to Healthy Aging : Stay Smart, Strong, and Active - Thompson, Edward H., Jr., 1945- (Book collections on Project MUSE., 2013)
As they reach middle age, most men begin looking forward to "what's next." They gear up to experience renewed productivity and purpose and are more conscious of their health. This is an authoritative resource for them, and for older men, as well. In collaboration with a variety of medical experts, the authors provide a comprehensive guide to healthy aging from a man's perspective. Refuting the ageist stereotype that men spend their later years "winding down," this book will help men reinvent themselves once, twice, or more - by managing their health, creating new careers, and contributing their skills and experiences to their communities.